Front Cover: In Situ Synchrotron X‐ray Diffraction Studies of the Mechanochemical Synthesis of ZnS from its Elements (Chem. Eur. J. 49/2021). Issue 49 (14th July 2021) - Petersen, Hilke; Reichle, Steffen; Leiting, Sebastian; Losch, Pit; Kersten, Wolfgang; Rathmann, Tobias; Tseng, Jochi; Etter, Martin; Schmidt, Wolfgang; Weidenthaler, Claudia
Abstract : The mechanism of the mechanochemical synthesis of cubic ZnS from its elements via ball milling was studied by in situ synchrotron diffraction experiments coupled with gas pressure measurements inside the milling vessel. The combination of both techniques reveals a heterogeneous reaction mechanism including gaseous sulfur and solid zinc. Moreover, the reaction kinetics of the phase transition from cubic to hexagonal ZnS was determined from the in situ synchrotron diffraction experiments. More information can be found in the Full Paper by C. Weidenthaler et al. (DOI: 10.1002/chem.202101260 ).